Noblesse Oblige! Membangun Semangat Zaman, Menuju Kebangkitan Ekonomi Negeri: Konteks Indonesia - Abdullah, Burhanuddin (SOSIOHUMANIKA, 2008)
ABSTRACT: In this early of 21st century, Indonesians are currently facing weighty challenges. The social contract between the citizens and the government that was made during the establishment of the Unitary State of the Republic of Indonesia is now under a threat such as bleak economy caused by poverty and social problems. There is no other way to escape from the threat but to forestall by implementing integrated economic development plans nationally. The implementation of the economic plans aforementioned would not possibly be detached of the roles of human beings as human capital and man of culture that are involved directly in the process of developing and re-building the Indonesia nation. In relation to this matter, this paper discusses one part of the cultural dimension, i.e. ethos or characters possessed by a group of people and used as their foundation to work. In âre-buildingâ the country, Indonesians are in need of a group of agents of development who can revive the new and better soul of age (zeitgeist) in this Reform era. The zeitgeist can only appear if those agents are familiar with ethos upheld by the former ones, that is Noblesse Oblige, which means that inside the specialty, power and authority are inherent with responsibility to the people.Â  Therefore, the agents are the people who have important roles and positions in re-building the economy of Indonesia in pursue of the realization of the nation-state aspiration to become a truly developed, harmonious, and free nation. Key word: economic crisis, to re-build the social contract among the citizens, positions and roles of the statesmen, and aspirations of Indonesian people in economy and politics.Â About the Author: Dr. Ir. Burhanuddin Abdullah, M.A. adalah Gubernur BI (Bank Indonesia) di Jakarta periode 2003-2008; dan anggota MWA (Majelis Wali Amanah) UPI di Bandung. Lahir di Garut, Jawa Barat, pada tahun 1947. Menyelesaikan pendidikan Sarjana (Ir.) di Fakultas Pertanian UNPAD (Universitas Padjadjaran) Bandung tahun 1974; Master of Arts (M.A.) di bidang ekonomi dari Michigan State University, Amerika Serikat, tahun 1984; dan Doktor (Honoris Causa) di bidang ekonomi dari UNDIP (Universitas Diponegoro) Semarang, Jawa Tengah, tahun 2006, dan UNPAD Bandung, tahun 2007. Menulis buku, di antaranya adalah Menanti Kemakmuran Negeri: Kumpulan Esai tentang Pembangunan Sosial Ekonomi Indonesia (Jakarta: PT Gramedia Pustaka Utama, 2006). Untuk keperluan akademik, beliau dapat dihubungi dengan alamat kantor:Â  Gubernur Bank Indonesia, Gedung Sjafruddin Prawiranegara Lt.3 Bank Indonesia, Jalan M.H. Thamrin No.2 Jakarta 10350. E-mail: aspensi@yahoo.comHow to cite this article? Abdullah, Burhanuddin. (2008). âNoblesse Oblige! Membangun Semangat Zaman, Menuju Kebangkitan Ekonomi Negeri: Konteks Indonesiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.1, No.1 [Mei]. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112, pp.69-78.Chronicle of the article: Accepted (February 19, 2008); Revised (April 5, 2008); and Published (May 20, 2008).